Conceptual data model for system resilience characterization. Issue 2 (11th November 2021) - Laun, Alexander; Mazzuchi, Thomas A.; Sarkani, Shahram
Abstract: Naval leaders are increasingly demanding resilient maritime systems capable of effectively anticipating, responding to, recovering from, and adapting to a given environmental disruption. For engineers designing these systems, real‐world data, information, and knowledge must be leveraged to operationalize the concept of resilience, particularly during the verification process of the system life cycle. However, such data are commonly unstructured, poorly organized, and lacking in context. Resilience‐defining data may not even exist, necessitating a methodological approach to ensure that relevant data are actually collected during system operation. This paper presents a feasible conceptual data model to improve the process of characterizing a given system's resilient performance. The authors consider the prevailing literature from the systems engineering, resilience engineering, and data management communities, and a scenario involving a hurricane‐impacted ocean monitoring system is presented as a case study of the conceptual data model's utility. Ultimately, by using a resilience‐centric data modeling approach, systems engineers can better derive prescribed resilience measures and metrics for a given system or system‐of‐systems.